The Effect of Carrageenan Concentration on the Quality of Soursop Jam Sheet During Storage - Ahmad Chairi; Herla Rusmarilin; Ridwansyah Ridwansyah (Universitas Sumatera Utara, 2014)
Soursop production in Indonesia is very abundant, but its processing is still very minimal, therefore the diversification of soursop processing is needed to increase. This study was conducted to determine the effect of carrageenan concentration on the quality of soursop jam sheet during storage. This study used a completely randomized design with two factors namely carrageenan concentration (K): 2,5%, 3,5%, 4,5% and 5,5%, and storage time (L): 0 days, 5 days, 10 days and 15 days. The parameters analyzed were moisture content, total acid, vitamin C, total dissolved solids, fiber content, total microbes, color and texture scores as well as organoleptic values of color, aroma, taste and texture. The results showed that the concentration of carrageenan had highly significant effect on water content, total acid, vitamin C, total dissolved solids, fiber content, color scores, texture scores as well as organoleptic of color, taste and texture. Storage time had highly significant effect on water content, total acid, total dissolved solids, total microbes, color scores, texture scores as well as organoleptic of color, aroma and texture. Interaction of the two factors had highly significant effect on water content and test scores texture. Concentration of 3,5% carrageenan gave the best quality characteristics of the soursop jam sheet and storage for 10 days was still acceptable for consumption. Keywords: Carrageenan concentration, soursop, Jam sheet, storage time.